Oleogelation of rapeseed oil with cellulose fibers as an innovative strategy for palm oil substitution in chocolate spreads. (March 2021) - David, Annabelle; David, Mélissa; Lesniarek, Pauline; Corfias, Emmanuel; Pululu, Yoann; Delample, Mathieu; Snabre, Patrick
Abstract: The texturing properties of mercerized cellulose dispersed in rapeseed oil without any prior thermal treatment were investigated as a function of botanical origin, cellulose content, mass fraction and fiber size through a molecular analysis of samples, macroscopic/microscopic observations and rheological experiments (continuous and oscillatory shear flows). A solid-like behavior of dispersions was demonstrated for a minimum cellulose content of about 60wt% in the vegetal powder. The oleogelation efficiency increases with the mass fraction of powder in oil and the maximum size of cellulose fibers as a result of weak attractive interactions and fiber entanglement giving rise to a network entrapping the liquid phase. An innovative strategy using a 30wt% dispersion of bamboo fibers in rapeseed oil was finally used to produce in a conch a chocolate spread with a high thermal stability at 38°C and healthier nutritional qualities compared to an equivalent product prepared with palm oil. Highlights: Oleogelation of an edible oil with cellulose fibers without treatment. Rapeseed oil texturing requires a minimum cellulose content of 60 wt%. Oleogelation results from weak attractive interactions and fiber entanglement. Use of cellulose fibers for palm oil substitution. Higher thermal stability of healthier chocolate spreads after palm oil substitution.